NILAI-NILAI PENDIDIKAN ISLAM DALAM BUKU TUHAN TIDAK PERLU DIBELA KARYA K.H ABDURRAHMAN WAHID - As’at Nursalim Ma’as Hamzah; Ahmad Subekti; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The contents of this book discuss problems that occurred between the late 1960-1970, these problems were Abdurrahman Wahid's attention to the Muslim community's rigid mindset in interpreting religion, religious teachings defined as limited rules that did not provide space to harmonize religious teachings with a problem that changes with the times. What results from these thoughts is the existence of increasingly isolated religion, showing that religious teachings are not in accordance with the times, showing that religion brings specific teachings to its people, so that what is seen in religion is anger everywhere by Islamic law enforcers. Using the literature study method the researcher obtains messages of Islamic education in the ideas and thoughts of Abdurrahman Wahid, the contents of his ideas are to link religious teachings with everything contained in life, such as upholding human values, values of social plurality and culture, including responding to contemporary problems. His ideas adjust the reality of life on the grounds that the interpretation of the scriptures as a guide need not be in the name of God let alone to defend God, but must be based on human interests and all aspects of humanity.